Chapter Examining Non‐Celiac Consumers of Gluten‐Free Products: An Empirical Evidence in Spain - Hellali, Wajdi (InTechOpen, 2017)
Energy‐dependent full‐field transmission soft X‐ray microscopy is a powerful technique that provides chemical information with spatial resolution at the nanoscale. Oxygen K‐level transitions can be optimally detected, and we used this technique to study the discharge products of lithium‐oxygen batteries, where this element undergoes a complex chemistry, involving at least three different oxidation states and formation of nanostructured deposits. We unambiguously demonstrated the presence of significant amounts of superoxide forming a composite with peroxide, and secondary products such as carbonates or hydroxide. In this chapter, we describe the technique from the fundamental to the observation of discharged electrodes to illustrate how this tool can help obtaining a more comprehensive view of the phenomena taking place in metal air batteries and any system involving nanomaterials with a complex chemistry.